Identity formation of the female adolescent character Kiki in Hayao Miyazaki’s anime Kiki’s Delivery Service - Mahanani, Prakerti Tyas; Noviana, Fajria (Universitas Dian Nuswantoro, 2025)
This study examines the process of Kiki's identity formation as a female adolescent in the anime Kiki's Delivery Service by Hayao Miyazaki, using Erik Erikson's psychosocial theory of identity, and the concept of femininity training from Takie Sugiyama Lebra. The study aims to describe the dynamics of Kiki’s psychosocial development as the main character, which reflects the stages of adolescent identity formation. This research employs a descriptive qualitative method with close-viewing and scene documentation techniques, with data consisting of dialogues, actions, and visual narratives in the form of screenshots from the anime. The results of the analysis indicate that Kiki’s journey corresponds to Erikson’s stages of identity formation, comprising three phases: the phase of initial idealism, the phase of identity crisis, and the phase of identity integration. The concept of femininity training by Lebra apparently does not significantly influence Kiki in her journey to find her identity; in fact, she tends to show the opposite. Thus, the formation of Kiki's self-identity not only signifies self-recovery but also emphasizes the importance of reflective space and social support in forming a complete and independent female adolescent identity.